2019
DOI: 10.3889/oamjms.2019.467
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Haramounting Leaf Ethanol Extract (Rhodomyrtus tomentosa (Aiton) Hassk.) on the Number of Leukocyte Type and Histology of Mice Pulmo (Mus Musculus L.) Exposed to Electronic Cigarette

Abstract: BACKGROUND: Haramonting leaves have a large antioxidant activity as inhibitors oxidation and form non-free radical compounds that are not reactive and relatively stable. Electronic smoking is a choice who slowly want to quit conventional smoking.AIM: This research aimed to determine the effect of ethanol extract on hard mounting leaves on leukocyte counts and histology Pulmo on male mice exposed to an electronic cigarette.METHODS: The samples used in this study were healthy male mice aged 8-11 weeks and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…R. tomentosa can also reduce HIF1α better in trophoblast cells aged 8 weeks compared to Zanthoxylum acanthopodium (Situmorang et al, 2022). These plants can decrease lipid peroxidation, enhance the expression of HSP-70, boost the capacity to scavenge free radicals, and improve the histology of the placenta, testis, and lungs (Ilyas and Situmorang, 2021;Ilyas et al, 2019;Irianti et al, 2020;Situmorang and Ilyas, 2018;Situmorang et al, 2020) Due to the high amount of phenolic. It has a strong antioxidant capacity and the potential to be a source of substances that improve health (Vo and Ngo, 2019).…”
Section: Important Angiogenesis Regulators Vegf Andmentioning
confidence: 99%
“…R. tomentosa can also reduce HIF1α better in trophoblast cells aged 8 weeks compared to Zanthoxylum acanthopodium (Situmorang et al, 2022). These plants can decrease lipid peroxidation, enhance the expression of HSP-70, boost the capacity to scavenge free radicals, and improve the histology of the placenta, testis, and lungs (Ilyas and Situmorang, 2021;Ilyas et al, 2019;Irianti et al, 2020;Situmorang and Ilyas, 2018;Situmorang et al, 2020) Due to the high amount of phenolic. It has a strong antioxidant capacity and the potential to be a source of substances that improve health (Vo and Ngo, 2019).…”
Section: Important Angiogenesis Regulators Vegf Andmentioning
confidence: 99%
“…Acclimatisation: The rats were acclimatized for 2 months before being treated in the laboratory in an air-conditioned room with a 12-hour light/dark cycle. Male rats are separated from female rats (Ilyas et al, 2019) 2. Diet for the animals: Rats were fed conventional laboratory diets in the form of pellets and corn and given free access to water.…”
Section: Animal Handlingmentioning
confidence: 99%
“…Diet for the animals: Rats were fed conventional laboratory diets in the form of pellets and corn and given free access to water. Food was provided ad libitum (Ilyas et al, 2019). 3.…”
Section: Animal Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…An examination of the pharmacological activity of Rhodomyrtus tomentosa revealed that this edible medicinal herb has antibacterial, antitumor, anti-inflammatory and antioxidant properties both in vivo and in vitro 3 . This herb can reduce lipid peroxidation, increase HSP-70 expression, improve free radical scavenging capacity and improve the histology of placenta and diabetic wounds [4][5][6][7][8] . It has a high antioxidant capacity and is a potential source of health-promoting substances due to its high phenolic content 9 .…”
Section: Introductionmentioning
confidence: 99%